1985
DOI: 10.1258/002367785780893575
|View full text |Cite
|
Sign up to set email alerts
|

A new diabetic strain of rat (WBN/Kob)

Abstract: A new, spontaneously occurring diabetic syndrome has been observed in the aged males of an inbred strain of Wistar rats, WBN/Kob. The main clinical sign, glycosuria, was first detected at about 60 weeks of age, and thereafter some animals developed hyperlipidaemia and gradual emaciation. Prior to the onset of glucosuria, male rats showed impaired glucose tolerance after a glucose load at 21 weeks of age. The histopathologic lesions of the pancreas in the diabetic males consisted of multifocal fibrosis, decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 8 publications
5
47
0
Order By: Relevance
“…In WBN/kob rat, myelinopathy and axonopathy with myelinated fiber loss caused by subsequent chronic pancreatitis and hyperglycemia have also been reported [16,19,28,33]. We consider that continuous hyperglycemia or hyperinsulinemia from a young age in TSOD mice might affect the peripheral nerves metabolically [34].…”
Section: Discussionmentioning
confidence: 84%
“…In WBN/kob rat, myelinopathy and axonopathy with myelinated fiber loss caused by subsequent chronic pancreatitis and hyperglycemia have also been reported [16,19,28,33]. We consider that continuous hyperglycemia or hyperinsulinemia from a young age in TSOD mice might affect the peripheral nerves metabolically [34].…”
Section: Discussionmentioning
confidence: 84%
“…These findings suggest a dysfunction of the intracellular Ca 2+ handling system in the spontaneously diabetic heart, which is likely to include impaired Ca 2+ sequestration and/or extrusion. The WBN/Kob (Wistar Bonn/Kobori) rat is an inbred strain of Wistar rat in which the male rats develop diabetes between the ages of 9 and 15 months [41,42,44]. Tsuchida et al [41] demonstrated abnormal ventricular function in 8 to 19-month-old male WBN/Kob rats, and showed that these rats resemble the NIDDM model, to some extent, in terms of the slow progression of pathophysiological change and a long span without insulin administration.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests possible differences of electrophysiological and mechanical properties between STZ-treated diabetic rats and spontaneously diabetic rats. It has been reported that male WBN/Kob rats spontaneously develop DM between the ages of 9 and 15 months [41,42,44]. However, acute pancreatitis and the pancreatic fibrosis were found even in 2-3 month-old WBN/Kob rats [18,43].…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous diabetic syndrome has been reported in aged males of the WBN/Kob rat strain [15][16][17][18][19][20][21][22]. These animals show reduced glucose tolerance at 5 months of age and develop the spontaneous diabetic syndrome around 9 months of age [18].…”
Section: Discussionmentioning
confidence: 99%